[Spatiotemporal variations of natural wetland CH4 emissions over China under future climate change] - Liu, Jian-gong; Zhu, Qiu-an; Shen, Yan; Yang, Yan-zheng; Luo, Yun-peng; Peng, Chang-hui (Ying Yong Sheng Tai Xue Bao = The Journal of Applied Ecology, 2015)
Based on a new process-based model, TRIPLEX-GHG, this paper analyzed the spatio-temporal variations of natural wetland CH4 emissions over China under different future climate change scenarios. When natural wetland distributions were fixed, the amount of CH4 emissions from natural wetland ecosystem over China would increase by 32.0%, 55.3% and 90.8% by the end of 21st century under three representative concentration pathways (RCPs) scenarios, RCP2. 6, RCP4.5 and RCP8.5, respectively, compared with the current level. Southern China would have higher CH4 emissions compared to that from central and northern China. Besides, there would be relatively low emission fluxes in western China while relatively high emission fluxes in eastern China. Spatially, the areas with relatively high CH4 emission fluxes would be concentrated in the middle-lower reaches of the Yangtze River, the Northeast and the coasts of the Pearl River. In the future, most natural wetlands would emit more CH4 for RCP4.5 and RCP8.5 than that of 2005. However, under RCP2.6 scenario, the increasing trend would be curbed and CH4 emissions (especially from the Qinghai-Tibet Plateau) begin to decrease in the late 21st century.
Keywords: Air Pollutants; China; Climate Change; Environmental Monitoring; Methane; Spatio-Temporal Analysis; Wetlands

Development and Evaluation of Models for the Relationship between Tree Height and Diameter at Breast Height for Chinese-Fir Plantations in Subtropical China - Li, Yan-qiong; Deng, Xiang-wen; Huang, Zhi-hong; Xiang, Wen-hua; Yan, Wen-de; Lei, Pi-feng; Zhou, Xiao-lu; Peng, Chang-hui (PLOS ONE, 2015)